Serum Zinc Levels in Celiac Paediatric Patients on Gluten Free Diet - Elsumdi, Hanan; Abdalla Rfieda, (AlQalam Journal of Medical and Applied Sciences, 2024)
Celiac disease is an autoimmune disorder with both genetic and environmental factors involved in its pathogenesis. It characterizes by small intestinal atrophy and malabsorption of essential nutrients, vitamins and trace elements due to ingestion of gluten. Zinc is an essential trace element for maintaining integrity of intestinal mucosa, immunity, and growth in children. Therefore, the aim of this study is to evaluate serum zinc levels in celiac paediatric patients on Gluten Free Diet (GFD) and compares it with healthy children. Sera of 22 celiac paediatric patients on GFD and 16 healthy children as a control group were obtained. The samples were prepared and zinc level was estimated via atomic emission spectrophotometer. Ninety one percent of celiac children on GFD had low zinc. The median plasma zinc concentration was significantly lower in celiac children on GFD (0.20 μg/ml) versus controls (0.86 μg/ml) with p value of < 0.0001. The current study shows that serum zinc concentrations are decreased significantly in celiac paediatric patients on GFD, suggesting zinc deficiency. Thus, good dietary guidance, zinc supplement therapy, and regular monitoring of zinc levels are highly recommended for celiac children on GFD. داء السيلياك (داء حساسية الغلوتين) هو اضطراب مناعي ذاتي تُساهم العوامل الوراثية والبيئية في إمراضه و تطوره. يتميز بضمور الأمعاء الدقيقة وسوء امتصاص العناصر الغذائية الأساسية والفيتامينات والعناصر النَّزِرة نتيجة تناول الغلوتين. يُعد الزنك عنصرًا نزرًا أساسيًا للحفاظ على سلامة الغشاء المخاطي للأمعاء، ودعم المناعة، والنمو لدى الأطفال. لذلك، يهدف هذا البحث إلى تقييم مستويات الزنك في البلازما لدى الأطفال المصابين بداء السيلياك الذين يتبعون نظامًا غذائيًا خاليًا من الغلوتين، ومقارنتها بالأطفال غير المصابين بالداء. تم جمع عينات مصل الدم من 22 طفلًا مصابًا بداء السيلياك ويتبعون نظامًا غذائيًا خاليًا من الغلوتين، بالإضافة إلى 16 طفلًا غير مصاب كمجموعةٍ مرجعية. تم تحضير العينات وقياس مستوى الزنك باستخدام مطياف الانبعاث الذري. تبين أن 91% من الأطفال المصابين بداء السيلياك والذين يتبعون نظامًا غذائيًا خاليًا من الغلوتين يعانون من نقص الزنك. وكان متوسط قيمة تركيز الزنك في البلازما لدى هؤلاء الأطفال (0.20 ميكروغرام/مل)، وهي أقل بكثير مقارنة بالأطفال غير المصابين (0.86 ميكروغرام/مل)، مع قيمة احتمالية p < 0.0001. تُظهر الدراسة الحالية أن مستويات الزنك في البلازما منخفضة لدى الأطفال المصابين بداء السيلياك الذين يتبعون نظامًا غذائيًا خاليًا من الغلوتين، مما يشير إلى انتشار نقص الزنك لديهم. لذا، يُوصى بشدة بتقديم إرشادات غذائية مناسبة، وتوفير مكملات الزنك، ومراقبة مستويات الزنك بشكل دوري لدى هؤلاء الأطفال